STUDENTS’ REPRESENTATION PROFILE IN SOLVING HOTS-BASED PROBLEMS IN CLASS VIII OF SMPN 3 TOLITOLI BASED ON GENDER - Khasanah, Tri Nur; Alfisyahra, Alfisyahra; Pathuddin, Pathuddin; Lefrida, Rita (Prima: Jurnal Pendidikan Matematika, 2025)
This study aims to describe the students' representation profile in solving Higher Order Thinking Skills (HOTS) based problems on chance material in class VIII of SMPN 3 Tolitoli, in terms of gender. The representations studied include three aspects: visual, verbal, and symbolic. This research used descriptive method with qualitative approach. The research subjects consisted of two students with high mathematical ability, one male student and one female student. Data were collected through HOTS-based tests and in-depth interviews. The results showed that male students tended to excel in visual and symbolic representations, able to present data in the form of diagrams and solve problems using mathematical expressions well. On the other hand, female students are more dominant in verbal representations, especially in writing down interpretations and solution steps in detail. This research emphasizes the importance of a representation-based learning approach to improve students' higher order thinking skills, taking into account the characteristics and advantages of each subject.